2023
DOI: 10.1039/d3cp00552f
|View full text |Cite
|
Sign up to set email alerts
|

Proton-donating and chemistry-dependent buffering capability of amino acids for the hydrogen evolution reaction

Abstract: The hydrogen evolution reaction (HER) has been widely demonstrated to have a strong dependence on pH and on the source of protons, where a clear kinetic advantage arises in acidic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Even so, proton transfer groups can help overcome this challenge by serving as proton relays to the active site, thereby increasing the local proton concentration. This hypothesis is supported by previous literature which has shown that proton-donating groups in the vicinity of the catalyst can effectively accelerate HER kinetics. The different dependences of the NO 3 RR and the HER on proton transfer can help us understand the support effect discovered in this study. With functional groups that can help transfer protons, the OCNT support promotes H 2 evolution but not NO 3 – reduction.…”
Section: Resultssupporting
confidence: 86%
“…Even so, proton transfer groups can help overcome this challenge by serving as proton relays to the active site, thereby increasing the local proton concentration. This hypothesis is supported by previous literature which has shown that proton-donating groups in the vicinity of the catalyst can effectively accelerate HER kinetics. The different dependences of the NO 3 RR and the HER on proton transfer can help us understand the support effect discovered in this study. With functional groups that can help transfer protons, the OCNT support promotes H 2 evolution but not NO 3 – reduction.…”
Section: Resultssupporting
confidence: 86%